Ex vivo Stimulation of Lymphocytes with IL-10 Mimics Sepsis-Induced Intrinsic T-Cell Alterations. (17th February 2018) - Poujol, Fanny; Monneret, Guillaume; Gallet-Gorius, Emmanuelle; Pachot, Alexandre; Textoris, Julien; Venet, Fabienne
ABSTRACT: Profound T-cell alterations are observed in septic patients in association with increased risk of secondary infection and mortality. The pathophysiological mechanisms leading to such dysfunctions are not completely understood and direct and indirect mechanisms have been described. In this study we evaluated whether ex vivo stimulation of lymphocytes with IL-10, an immunosuppressive cytokine released at the systemic level during sepsis, could mimic sepsis-induced intrinsic T-cell alterations. We showed that recombinant human IL-10 priming of T cells altered their proliferative response to anti-CD2/CD3/CD28 antibody-coated beads and PHA stimulations, in a dose-dependent manner independently of accessory cells. This priming also significantly decreased T-cell secretion of IL-2 and IFNγ following stimulation. Furthermore, we demonstrated that IL-10 reduction of T-cell functionality was associated with increased FOXP3 expression in CD4 + CD25 + CD127 − regulatory T cells as observed in sepsis. Finally, we found that blocking the increased IL-10 concentration in plasma from septic shock patients increased the proliferative response of responding T cells from healthy controls. We describe here an ex vivo model recapitulating features of sepsis-induced intrinsic T-cell alterations. This should help, in further studies, to decipher the pathophysiological mechanisms of T-cell alterations induced after septic shock.